O Sistema de Informação/Arquivo da Faculdade de Ciências da Universidade do Porto: Estudo e implementação de um modelo de gestão da informação - Hugo Manuel Maciel Silva (2018)
In the midst of the 21st century, information is perceived as a valuable asset and resource to institutions and organizations, requiring a proper approach of the infocommunicational process and its management. It is, thus, understandable the relevance of the work developed within the scope of the project presented in this dissertation in Information Science, area of studies of Information Management (IM), that has, as its main goal, the contribution to the implementation of an Information Management (IM) model in an academic context - the Faculty of Sciences of the University of Porto (FCUP) -, the oldest school of U.Porto, along with the Faculty of Medicine. The Systemic Theory and the Quadripolar Method are part of the theoretical and methodological framework that supports the operationalization model which guided this project, focused on the infocommunicational flow - the Active and Permanent Universitary Information System Management Model (MGSI-AP) - affirming an holistic and dynamic view of the IM role. There are also contributions from Project Management methodology and Requirements Engineering. Funded in 1911, FCUP is one of the biggest faculties of U.Porto and, as a study object, presents a real challenge, either when considering its dimension and structural complexity or its institutional path and subsequent transformations. Initially, the proposal pointed to basic, but crucial, needs as to provide physical and intellectual control over archival materials, their organization, description and representation. However, owing to the changes that the existing applications of archive management have to face, it was also considered a theoretical reflexion around the most recent proposal of the International Council on Archives - the Records in contexts: a conceptual model for archival description (RiC-CM) - comparing this new guideline with existing archival standards. The projects results include a detailed Organic and Functional Study (1911-2018) and consequent proposal of a Classification Plan, the Mapping of Stored Archival Materials, a List of Archival Holdings produced by the institutional organs and Academic Services, the Mapping of Technological Systems, the modelling of processes and a Requirements Specification Document related to Mail Management and the FCUP Archive reinstallation guidelines. Keywords: Information Management, Archives Management, Organic Functional Analysis; RiC-CM, FCUP, University of Porto.